Popularizing Ecocriticism: A Study on Environmental Awareness among English Discipline Students at Khulna University - Neloy, Nowshad Hasan; Rahman Shahin, Abdur (Journal of Environmental and Science Education, 2025)
As global ecological crises increase, the role of literary studies in promoting environmental consciousness has garnered growing academic interest. Ecocriticism, a branch of literary criticism, helps learners analyze literature from the perspective of environmental issues. At Khulna University, students of the English Discipline show a strong appreciation for nature and an interest in preserving biodiversity. This study explores how ecocriticism can be used to enhance environmental awareness among these students. The aim of this study is to motivate students to engage with ecocriticism and to study literature in terms of environmental awareness. The research employed a mixed-methods approach. It included workshops, surveys, field visits, and focus group discussions. More than one hundred students and several faculty members of the English Discipline participated enthusiastically in the workshops. They watched video clips related to environmental disasters and struggles of the coastal people who are vulnerable to many environmental threats. The findings confirm a significant increase in students’ understanding of environmental issues, their enthusiasm to apply ecocritical frameworks in both academic and activist contexts, and their willingness to engage in sustainable practices. Thus, this study highlights the potential of literature as a transformative tool in promoting environmental responsibility within academic institutions.